Pastoral fattening with BMR (Brown Middle Rib) sorghums as fresh forage - Fern?ndez Mayer, A. E.; Stuart, Justiniano; Chongo, Bertha; Mart?n, Pedro C. (Cuban Journal of Agricultural Science, 2011)
Forage sorghums (Sorghum sp.), Sudan type, are quite used in Argentina as fresh forage due to their large production (8 to 15.000 kg DM ha-1), permitting to support high stocking rate (three to six animals ha-1) during the summer. Nevertheless, due to nutritional unbalances, daily weight gains (DWG) are low (400 to 600 g daily). The utilization of the new BMR sorghum (Brown Middle Rib) as fresh forage, whose quality is significantly higher with lower content of lignin, could improve the DWG and the finishing stage of the animals. With this object, a trial was conducted with Angus steers (British), grazing BMR sorghum as fresh forage without supplementation. The trial had two stages: 1st) 140 steers of 318 kg of LW animal-1 during 99 d and 2nd) 340 steers of 364 kg of LW animal-1 during 69 d. The nutritional quality, the forage assignation (Af), the daily weight gain, the conversion efficiency (CE) and the production costs (PC) were measured. The experimental unit corresponded to the animal, with 20 repetitions per stage. Linear models were tested. The in vitro DM digestibility of the two stages were of 76.73 and 77.06 %, respectively. The Af reached 4.54 and 4.64 kg DM, every 100 kg LW d-1. The DWG was of 0.788 and 0.801 kg animal-1 d-1, respectively. The CE was of 12.44 and 12.98 kg of DM of feed kg produced-1. The PC corresponded to 0.47 and 0.67 u$s kg produced-1. The slaughter weights were of 396 and 402.5 kg animal-1 respectively, and the PC were quite adequate for a pastoral system. Key words: pastoral, finishing stage, nutritional quality, British steers without supplement.